Virtual manufacturing for prediction of Martensite Formation and Hardness Value induced by Laser Welding Process using Subroutine Algorithm in MSC Marc/Mentat / Omar Yahya...[et al.] - Yahya, Omar; HP Manurung, Yupiter; Sulaiman, Mohd Shahar; Prajadhiana, Keval; Omar, Abdul Rahman; Kuntjoro, Wahyu (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
In this paper, a coupled thermal-structural and metallurgical model of laser welding process is simulated by using Finite Element Method (FEM) enhanced with Fortran-based subroutine within MSC Marc/Mentat. The investigated model specimen is in the form of butt joint plate with thickness of 2mm and material of low carbon steel (C15). The core purpose of the simulation is to predict Martensite formation and hardness value after laser welding process. In the simulation, a heat source model following conical shape is implemented instead of existing Goldak's double ellipsoid used commonly for arc welding process. The Martensite formation and hardness are predicted based on Seyyfarth-Kassatkin Model, the results of which are to be verified with the welding Continuous Cooling Transformation (CCT) diagram. It can be concluded that the algorithms to model the heat source and to calculate the cooling time t8/5 are successfully developed and implemented. The simulated heat source shape produced using conical model represents good similar feature with typical laser heat source. Based on the calculated t8/5, it is also found that the results of Martensite formation and hardness value show good agreement within acceptable discrepancy compared to the approximated analysis from CCT diagram.